If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -5 = 2x + 0 Reorder the terms: -5 + -1x = 2x + 0 Reorder the terms: -5 + -1x = 0 + 2x Remove the zero: -5 + -1x = 2x Solving -5 + -1x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -5 + -1x + -2x = 2x + -2x Combine like terms: -1x + -2x = -3x -5 + -3x = 2x + -2x Combine like terms: 2x + -2x = 0 -5 + -3x = 0 Add '5' to each side of the equation. -5 + 5 + -3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 0 + 5 -3x = 0 + 5 Combine like terms: 0 + 5 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667
| Cosx=27 | | 6x-5(20+2x)=12 | | 9xy-12xy= | | x*x-6*x-12=0 | | -9(k+11)=-288 | | 7x+18=85 | | -12-7a=-5(a+4) | | 45=x+62+x+87 | | 9x+13=59 | | 38x+31=563 | | -30-6x=-6(3x-7) | | 17x+6=106 | | 16-3m=7-6(m+2) | | 10x-25=105 | | 80+x=171 | | 34+4x=-5(x+4) | | -3x-3(1+1)=-15 | | 55x=605 | | 2x+-2=10-4 | | 4y+9=17-2y | | 43+x=410 | | x-24=64 | | -3X^2+90=0 | | 5x=430 | | 4x-5y-9x+8y=0 | | 2x^2-lnx+1=0 | | 90-x^2=0 | | -x+3+12x=-4+4x+42 | | 5x-15x^3=5x(1-3x^2) | | (x+8)+4=x+(4+8) | | 3w^2-10w+8=0 | | -4(2+3n)=-56 |